2011
DOI: 10.1007/s11104-011-0921-9
|View full text |Cite
|
Sign up to set email alerts
|

Selecting improved Lotus nodulating rhizobia to expedite the development of new forage species

Abstract: Aims In the past decades the increasing focus by Australian pasture development programs on the genus Lotus has seen the evaluation of many species previously untested in Australia. In field trials, nodulation failure was commonplace. This work was undertaken to select effective symbionts for Lotus to ensure further agronomic evaluation of the genus was not compromised. The symbiotic needs of Lotus ornithopodioides were a particular focus of the studies.Methods Glasshouse experiments were undertaken to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Also mesorhizobia strains isolated from L. oroboides in Mexico failed to nodulate L. corniculatus although unfortunately no other Lotus were tested ( Qian and Parker, 2002 ). Neither of the Australian commercial inoculant strains for L. uliginosus (CC829) and L. corniculatus (SU343) can fix nitrogen with the promising forage species L. ornithopodioides ( Howieson et al, 2011 ). Indeed, these authors found no strains compatible with all the 15 Lotus species evaluated.…”
Section: Specificity Of the Rhizobia- Lotus Symbiomentioning
confidence: 99%
See 2 more Smart Citations
“…Also mesorhizobia strains isolated from L. oroboides in Mexico failed to nodulate L. corniculatus although unfortunately no other Lotus were tested ( Qian and Parker, 2002 ). Neither of the Australian commercial inoculant strains for L. uliginosus (CC829) and L. corniculatus (SU343) can fix nitrogen with the promising forage species L. ornithopodioides ( Howieson et al, 2011 ). Indeed, these authors found no strains compatible with all the 15 Lotus species evaluated.…”
Section: Specificity Of the Rhizobia- Lotus Symbiomentioning
confidence: 99%
“…In some cases, the uncertainty about the bacterial origin can lead to uncertainty about its symbiotic properties. For instance, it is unclear if SU343 (equivalent names NZP 2196, ICMP 3663, ICMP 10808, PDDCC 3663, ATCC 35173, DSM 6046) was originally isolated from L. corniculatus in United States (as described for ICMP10808 and mentioned in Howieson et al, 2011 ), or from Lupinus sp. in Australia (as for ICMP 3663/NZP2196 and ATCC 35173, and in Charlton et al, 1981 ).…”
Section: Lotus Rhizobial Inoculantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains used for the inoculation of M. sativa, Lotus spp. and H. coronarium were selected as effective strains for these species, with some strains used as commercial inoculants in Australia (Langer et al, 2008;de Koning et al, 2010;Howieson et al, 2011). In this study, strain WSM2141 was found in most of the nodules from M. sativa two months after sowing and in 32% of the nodules a year later; however, in L. corniculatus, L. tenuis and H. coronarium, the inoculant strains were completely displaced by soil rhizobia.…”
Section: Discussionmentioning
confidence: 64%
“…Las plantas leguminosas tienen altos requerimientos en fósforo y potasio, caso contrario ocurre con el N mineral, ya que son capaces de fijar suficientes cantidades a través de la fijación biológica de N (Howieson et al, 2011). Estas plantas son sensibles a las deficiencias de fósforo, potasio y azufre, nutrientes que afectan de manera directa la fijación biológica de nitrógeno, e indirectamente el crecimiento de la leguminosa (Divito & Sadras, 2014).…”
Section: Resultados Y Discusiónunclassified